Pengaruh Media Tebak Gambar Terhadap Keterampilan Berbahasa Pada Siswa Kelas SD Negeri 05 Mendo Barat - Linda Lestari; Dian Nuzualia Armariena; Rury Rizhardi (Universitas PGRI Adi Buana Surabaya, 2021)
This research is motivated by the fact that language skills, especially the speaking skills of third grade students of SD Negeri 05 Mendo Barat have not been maximized, especially inthe learning process. This study aims to determine whether or not there is an effect of image guessing media on speaking skill singrade III students SD Negeri 05 Mendo Barat. The method in this study used a pre-experimental design with the one-group pretest-posttest design research design. The population in this study were all third grade students who took part in learning at SD Negeri 05 Mendo Barat. Sampling in this study is using a total sampling technique of 30 students. The research process was carried out in accordance with the steps that have been determined through the assessment of speaking skills based on image stimulation by Nurgiyantoro (2012). In this study, researchers conducted data analysis techniques, namely using the t test. Based on the data analysis that has been carried out the t test shows the value of t =9.742is more than t table(0.05)(dk=n-1)=2.045 so that H0 is rejected. As for the sig. equal to 0.000 <0.025. It can be concluded that there is an influence of the image guessing media on thes peaking skills of students in class III SD Negeri 05 Mendo Barat.